2012
DOI: 10.2485/jhtb.21.351
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Surface Structure and Bio-Absorption of Human Dentin Granules Designed by the Supersonic Demineralization and Biomimetic Coating Technique

Abstract: Demineralized dentin matrix (DDM) granules with excellent biocompatibility were designed using extracted human teeth by the cooling-pulverizing and supersonic demineralizing technique. Extracted teeth were pulverized together with saline ice at 12,000 rpm of a ZrO2 blade for 30 s in a ZrO2 vessel. The pulverized granules having 0.5-2.0 mm in granular size were dissolved by the supersonic treatment at 120 W and 38 kHz or 600 W and 28-100 kHz in 2.0 % HNO3 solutions to obtain partially or completely DDM granules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Supersonic demineralization produced more nano- and micro-cracks, which increased the effective surface area. Thus, the body fluid will smoothly permeate through the micro-cracks in the PR-DDM [ 33 ]. These observations are scientifically important for hard tissue-derived graft material processing procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supersonic demineralization produced more nano- and micro-cracks, which increased the effective surface area. Thus, the body fluid will smoothly permeate through the micro-cracks in the PR-DDM [ 33 ]. These observations are scientifically important for hard tissue-derived graft material processing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Co., Ltd., Seoul, Korea) in 5 L of 0.34 N HNO 3 solutions at 100 W and 60 kHz for 30 min. The liquid temperature of the sample gradually increased with an increasing supersonic time up to 30 min, but they were maintained at less than 315 K to avoid denaturing proteins, as previously reported [ 33 ]. Finally, we used an extensive rinse with DW to prepare the PR-DDM.…”
Section: Methodsmentioning
confidence: 99%
“…It is recently shown that the surface area, tube diameter and length increase in dentin treated by ultrasonic irradiation with AEW in time dependent manner 14 . Result from our experiment was consistent to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Interconnected macropore structure is necessary to promote body fluid permeation, neovascularization, and cell migration to the central pores, and micropores can provide more nucleation sites for bone-like apatite precipitation [ 22 , 23 ]. The supersonic acid-demineralization produces biologically simulant microcracks on the surface and inner bulk of commercial HAp products for precipitation of nano/micro crystals [ 19 , 24 ]. Additionally, all biomaterials, used for bone regeneration, should enhance bone growth directly in contact with the biomaterial surface from the surrounding bone, but it should also be capable of inducing osteoinduction [ 25 ].…”
Section: Introductionmentioning
confidence: 99%